Danish literature from 1000 to 1900 - Mai, Anne-Marie 1953- (University of Southern Denmark studies in Scandinavian languages and literatures, 2022)
Danish Literature from 1000 to 1900 is an inclusive and networked literary history that does not turn literary texts into mute museum pieces. The volume includes an analysis of the world famous Danish History of Saxo Grammaticus of the middle ages as well as a presentation of the renaissance masterpiece, Memoirs, by Leonora Christina Ulfeldt. The writings of the leading enlightenment author, Ludvig Holberg, are also introduced and the romanticist novelist Thomasine Gyllembourg, the fairytale author Hans Christian Andersen and the philosopher Søren Kierkegaard are key figures of the historic exposition. The volume is concluded by an introduction to the authors of the modern breakthrough. Central international contributions to literary studies and extensive discussion on periodization is included in Danish Literature from 1000 to 1900 so that readers may relate this periodization to the periodization of other national literatures. The volume also includes chronological overviews and notes on literary studies? discussion of historiography and influential recent research and approaches to Danish literature.